Use of apoptosis, oxidative stress and specific cardiovascular biomarkers to demonstrate myocardial damage in neonatal calves infected with different infectious agents - Uztimur, Murat; Dortbudak, Muhammed Bahaeeddin; Unal, Cennet Nur; Sagiroglu, Meltem (Academic Press Ltd- Elsevier Science Ltd, 2025)
In human medicine, there is evidence to suggest that myocarditis may be present in cases of diarrhea associated with various infectious agents. Nevertheless, the question of whether etiological agents cause myocardial damage in calves with diarrhea remains unanswered in the field of veterinary medicine. Based on this, we aimed to determine the presence of myocardial damage, cellular oxidative damage and apoptosis in calves with sepsis using high-sensitivity biomarkers. The study material consisted of 55 acute diarrheal calves and ten healthy controls. The diarrheic calf group consisted of rotavirus (n = 10), coronavirus (n = 10), cryptosporidium parvum (C. parvum) (n = 10), giardia lamblia (n = 10), and non-survivors (n = 15). Cardiac histopathology and immunohistochemical (Heat shock proteins 27 and caspase 3) analyses were performed on 15 calves that did not survive the study. In sepsis calves, high sensitivity cardiac troponin-I, fatty acid binding protein 3, creatine kinase myocardial band, L-lactate, and anion gap concentrations were significantly higher than in the control group. In the histopathological examination of the heart of the calves that did not survive, degenerative-necrotic, cellular damage, inflammatory cell infiltration, and vascular changes were observed, while immunohistochemical examination determined that oxidative damage and intense apoptosis occurred. In conclusion, the presence of myocardial damage in sepsis calves was confirmed by both histopathological and immunohistochemical techniques and serum cardiac specific biomarker concentration analyses. It was also shown that anion gap, bicarbonate, and L-lactate also contribute to the formation of myocardial damage.
Keywords: Calf; Caspase; hsTnI; Myocardial damage; Sepsis